Ecotourism of Mangrove Beach Kampung Nipah Serdang Bedagai North Sumatra Indonesia - Indri Lestari; Ernawati; Rosdianto (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
The development of mangrove ecotourism in coastal areas has become an approach to maintaining ecosystem sustainability while supporting the welfare of local communities. Mangrove Beach Kampung Nipah in Serdang Bedagai Regency is a mangrove rehabilitation area that has developed into a community-based ecotourism destination. This study aims to analyze management conditions, the availability of facilities and infrastructure, and to formulate development strategies for Mangrove Beach Kampung Nipah from a sustainable tourism perspective. The research method employs a descriptive qualitative approach, with data collected through field observations, interviews, and literature review, and analyzed using descriptive analysis and SWOT analysis. The results indicate that ecotourism management is community-based through local institutions, supported by relatively adequate tourism facilities and diverse natural and educational tourism attractions. The SWOT analysis identifies strengths in mangrove rehabilitation and community-based management, as well as challenges related to accessibility, promotion, and the control of environmental carrying capacity. The implications of this study highlight the need to strengthen stakeholder collaboration, enhance human resource capacity, and implement tourism management based on environmental carrying capacity to support the sustainability of coastal ecotourism.